2020
DOI: 10.1002/tsm2.156
|View full text |Cite
|
Sign up to set email alerts
|

Identifying childhood movement profiles and tracking physical activity and sedentary time across 1 year

Abstract: This study identified movement profiles in childhood and tracked longitudinal changes in moderate‐to‐vigorous physical activity and sedentary time across identified profiles. A sample consisted of 491 Finnish 5th Grade children (girls 275, boys 216; Mage = 11.27 ± 0.32). A latent profile analysis strategy was used to identify homogenous movement profiles that included measures of motor competence, perceived competence, and cardiorespiratory and muscular fitness. To examine a 1‐year change in moderate‐to‐vigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
5
16
0
Order By: Relevance
“…Our findings are consistent with previous studies, which revealed three or four movement profiles 19,20 and demonstrated substantial differences in the MC and HRF variables among clusters. 20 Especially, rather large (n = 129, 28% of the total sample) cluster "poor movers" received much lower results in all physical measures than any other clusters.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous studies, which revealed three or four movement profiles 19,20 and demonstrated substantial differences in the MC and HRF variables among clusters. 20 Especially, rather large (n = 129, 28% of the total sample) cluster "poor movers" received much lower results in all physical measures than any other clusters.…”
Section: Discussionsupporting
confidence: 93%
“…18 Few cluster analytic studies have demonstrated that it is possible to identify different movement profiles from samples, including children and adolescents. According to results of these studies, identified profiles differ substantially in MC and cardiorespiratory and muscular fitness 19 , as well as PA engagement. 20 Children and adolescents who belong to clusters that have high MC typically demonstrate higher engagement in PA than youth who belong to clusters that demonstrate low qualities.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of children in the three fitness profiles was as expected, supporting the earlier findings with Finnish school children, 33 in which the variables included in the latent cluster analysis were exactly the same as in this study whereas the past total sample was smaller. It should be considered that the PMC scale used in the study was a holistic instrument for sports competence perceptions rather than perceived motor competence, which comprises subdomains of competence in stability, locomotion, object control, and active play skills.…”
Section: Discussionsupporting
confidence: 89%
“…The product-oriented locomotor skill test may require higher dynamic balance, speed, and lower limb strength than the other two MC tests used in this study, that is, the throw-catch and side-to-side jump tests, which in turn may reflect predominant contribution of five-leap test scores to PC. In conclusion, these findings support the importance of versatile MC acquisition in early childhood (44,49), starting in kindergarten and continuing across the primary school years.…”
Section: Discussionsupporting
confidence: 79%
“…The side-to-side, throw-catch, and five-leap test scores were standardized and summed to form an overall MC score. Further details on the present MC tests were recently reported (49).…”
Section: Methodsmentioning
confidence: 99%